Building trust in social commerce: A sequential model of platform features, marketing content, and dual trust in shaping Generation Z engagement - Rian Piarna; Dwi Vernanda; Tri Herdiawan Apandi (Universitas Islam Malang, 2025)
Social commerce has revolutionized the digital landscape, positioning social media as a primary shopping channel for Generation Z. Despite their intensive use of social media for commercial activities, limited research has examined the psychological mechanisms underlying customer engagement in this context. This study investigates how social media service features and social commerce marketing content sequentially influence customer engagement through trust-building mechanisms and purchase intention. Drawing on a dual trust perspective, distinguishing between platform trust and vendor trust, this research proposes and tests a sequential mediation model tailored to Generation Z consumers. A quantitative cross-sectional design was employed, using purposive sampling to collect data from 400 Generation Z respondents. The model was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results support the proposed sequential mediation model, with 10 of 15 hypotheses confirmed. Social proof proved to be the most important predictor of trust in a platform, whereas content quality affected both dimensions of trust (platform and vendor) across social commerce platforms. Personalization demonstrated the strongest effect on vendor trust. The model explains a substantial proportion of variance in platform trust, vendor trust, customer engagement, and purchase intention.